2012
DOI: 10.2169/internalmedicine.51.7547
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Adrenocorticotropic Hormone (ACTH)-independent Macroadrenal Hyperplasia Showing Ectopic Production of ACTH

Abstract: A 57-year-old Japanese man presented with drug-resistant hypertension without Cushingoid features. Endocrinological tests revealed autonomous secretion of cortisol with suppressed plasma adrenocorticotropic hormone (ACTH). Imaging examinations showed multiple macronodules in the bilateral adrenal gland. These findings were consistent with subclinical Cushing's syndrome caused by ACTH-independent macronodular adrenal hyperplasia (AIMAH). Left adrenalectomy was performed and the resected adrenal lesion was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Ectopic ACTH production was previously reported in steroidogenic cells in a few cases of BMAH [39,40]. A recent extensive study summarized here reveals that the paracrine production of ACTH was much more prevalent and under more complex regulation than previously recognized amplifying the effect of the aberrant receptors' ligands.…”
Section: Paracrine Production Of Adrenocorticotropic Hormone In Bilatmentioning
confidence: 53%
“…Ectopic ACTH production was previously reported in steroidogenic cells in a few cases of BMAH [39,40]. A recent extensive study summarized here reveals that the paracrine production of ACTH was much more prevalent and under more complex regulation than previously recognized amplifying the effect of the aberrant receptors' ligands.…”
Section: Paracrine Production Of Adrenocorticotropic Hormone In Bilatmentioning
confidence: 53%
“…However, Iwata et al . previously reported a case of bilateral macronodular adrenal hyperplasia showing ectopic production of corticotropin . After that, an analysis of 30 cases of bilateral macronodular adrenal hyperplasia with subclinical or overt Cushing's syndrome was carried out .…”
mentioning
confidence: 99%
“…However, Iwata et al previously reported a case of bilateral macronodular adrenal hyperplasia showing ectopic production of corticotropin. 3 After that, an analysis of 30 cases of bilateral macronodular adrenal hyperplasia with subclinical or overt Cushing's syndrome was carried out. 1 The adrenal tumors in our current two Japanese cases of bilateral macronodular adrenal hyperplasia showed that corticotropin is produced by a subpopulation of steroidogenic cells in the hyperplastic adrenals.…”
mentioning
confidence: 99%
“…This implies that ectopic production of ACTH might induce adrenocortical hyperplasia and cortisol secretion (Pereira et al 2001, Lefebvre et al 2003, Mazzuco et al 2007, Iwata et al 2012.…”
Section: Ectopic Expression Of Corticotropin In Pmahmentioning
confidence: 99%